L’occupation préhistorique du plateau de Gergovie (Puy-de-Dôme). Caractérisation des industries lithiques néolithiques - Jean-François Pasty (Revue Archéologique du Centre de la France)
The oldest traces of a continued occupation on the plateau of Gergovie date back to the Middle Neolithic period. The lithic finds come from casual collection points or from the excavations concentrated on more recent archaeological periods. The different techno-typological components identified document two periods from the Neolithic: the Chasseen recent and the Late Neolithic. The Chasseen is mainly characterized by the production of flakes debited by pressure, in tertiary flint, either local or imported from the Berry and the Rhone valley. The tools are represented by arrowheads and domestic tools (scrapers, burins, blades and retouched flakes, polished hand-axes). They indicate the presence of settlements and diversified activities on the plateau. The occupation seems less intense during the Late Neolithic, the stone objects are less abundant and are mainly represented by arrowheads.